KINERJA CUSTOMER SERVICE DITINJAU DARI DISIPLIN KERJA, PENGALAMAN KERJA, DAN GAJI - Aryanto, Tossy; Hartarini, Yovita Mumpuni; Tri Rochmawan, M Laksono (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of work discipline, work experience, and salary on customer service performance at PT JMTO Ruas Tol Semarang ABC. In this study, the population studied was all customer service employees at PT JMTO Ruas Semarang ABC, with a total of 71. The sample was taken using a purposive sampling technique. The sample criteria in this study were employees who had worked for more than one year. From this population, 60 respondents met the criteria. The quantitative research method used SPSS Version 26. Data analysis used multiple linear regression. The results showed that the instruments used had met the instrument test standards and passed the classical assumption test. Based on hypothesis testing, it was found that: (1) Work discipline has a positive and significant influence on employee performance, with a coefficient of work discipline variable (X1) of 0.342 (positive), a calculated t value of 4897 greater than the t table of 2.004, and a significance value of 0.00, so that there is a positive influence of work discipline (X1) on employee performance (Y). (2) Work experience has a positive and significant influence on purchasing decisions, with a coefficient of price variable (X2) of 0.451 (positive) a calculated t value of 6.029 greater than the t table of 2.004, and a significance value of 0.00, indicating a positive influence of work experience (X2) on employee performance (Y). (3) Salary has a positive and significant influence on employee performance, with a salary variable coefficient (X3) of 0.094 (positive) t-value of 2.418 greater than t-table 2.004, and a significance value of 0.00, indicating a positive influence of salary (X3) on employee performance (Y).. (4) Together, the variables Work discipline (X1), Work experience (X2), and Salary (X3) simultaneously affect employee performance (Y), as evidenced by the F-value of 65.580 greater than F-table 2.54 and a significance value of 0.00. Companies are advised to strengthen the culture of discipline at every level of the organization, provide development opportunities for customer service, and ensure competitive salaries according to employee contributions. For further research, expanding variables, qualitative approaches such as in-depth interviews, and implementing research in other sectors will help gain deeper insights and generalization of research results related to customer service performance.